El futuro contable en las empresas de seguros: la norma internacional de información financiera 17 contratos de seguros. - Piedra Luna, Jorge Humberto (My University, 2019)
The insurance industry has relevance in the world economy. After the financial crisis experienced globally, insurers are reorganizing their business strategies to obtain the greatest benefit from the benefits of economic recovery. Motivated by the request of the interested party, the governing body in accounting and financial matters, the International Accounting Standard Board, has developed an accounting framework to regulate this important sector of insurance companies and the disclosure of financial information with high standards of quality that serves as an aid to the investor or interested party at the time of making decisions. Twenty years after the predecessor of the IASB began the project of insurance contracts, the new accounting framework will replace International Financial Reporting Standard 4 for accounting periods beginning on January 1, 2021. This is an important milestone for the insurance industry, being the first accounting standard in a global way for insurance contracts. With its approval in May 2017, the International Financial Reporting Standard 17 incorporates unprecedented changes in the accounting of insurance contracts (issuers) and reinsurance contracts (holders and issuers), fundamentally, how and what should be taken into account at the moment of the preparation and elaboration of the financial statements. Against this, the objective of this research work is to expose various views of authors, by reviewing the approach that has been unified by the IASB for the correct application of this international regulation. The methodology applied in this work has been documentary research, which depends mainly on the information obtained or consulted in document, understood as all material that can be used as a reference source, without altering its nature or meaning, that provides information or gives testimony of a reality or event; who has been of great importance to determine that the regulations will cause a radical change. The IASB has developed IFRS 17 in order to increase comparability between the countries where this accounting framework applies, regardless of whether the entity is regulated as an insurer or if a contract has characteristics that resemble insurance or reinsurance contracts. Result of the investigation has concluded the following: Apart from the change in the way in which the insurance companies are going to keep their accounts, the new accounting framework requires a significant implementation work in all its operations. This will lead to the inclusion of new technology or, at the same time, improve existing technology, optimize methods and renew controls. For the implementation of this new quality standard in insurance companies, it will be necessary to have competent internal or externally hired personnel not only to understand the impact of applying the new accounting framework of insurers, but also to implement it to the context of daily business. Insurance companies should carry out communication projects with investors in order to state that the implementation of IFRS 17 will lead to greater volatility in financial results, and the equity capital of which they are participants, originated by the use of the current market discount rates.
La industria de los seguros tiene relevancia en la economía mundial. Después de la crisis financiera que se vivió globalmente, las instituciones aseguradoras están reorganizando sus estrategias de negocios para obtener la mayor ventaja de los beneficios de la recuperación económica. Motivado por la petición de la parte interesada, el organismo rector en materia contable y financiera, el International Accounting Standard Board, ha desarrollado un marco contable para regular este importante sector de las empresas de seguros y de la revelación de información financiera con altos estándares de calidad que sirva de ayuda al inversionista o a parte interesada en el momento de tomar decisiones. Veinte años después de que el predecesor del IASB comenzara el proyecto de los contratos de seguros, el nuevo marco contable reemplazará a la Norma Internacional de Información Financiera 4 para ejercicios contables a partir del 1 de enero de 2021. Este se constituye como un importante hito para la industria de las aseguradoras al ser la primera norma contable de manera global para los contratos de seguros. Con su aprobación en mayo de 2017, la Norma Internacional de Información Financiera 17 incorpora cambios sin precedentes en la contabilización de contratos de seguros (emisores) y contratos de reaseguros (tenedores y emisores), fundamentalmente, cómo y qué deben tener en cuenta al momento de la preparación y la elaboración de los estados financieros. Frente a ello, el objetivo del presente trabajo de investigación es exponer diversos puntos de vistas de autores, mediante la revisión del enfoque que ha sido unificado por el IASB para la correcta aplicación de esta normativa internacional. La metodología aplicada en este trabajo ha sido la investigación documental, la cual depende fundamentalmente de la información que se obtiene o consulta en documento, entendiéndose como todo material al que se puede acudir como fuente de referencia, sin que se altere su naturaleza o sentido, que aporta información o da testimonio de una realidad o acontecimiento; quien ha sido de gran importancia para determinar que la normativa provocará un cambio radical. El IASB ha desarrollado la NIIF 17 con la finalidad de incrementar la comparabilidad entre los países donde se aplica este marco contable, independientemente de que la entidad este regulada como aseguradora o si un contrato tiene características que se asemejen a contratos de seguro o reaseguro. Resultado de la investigación se ha concluido lo siguiente: Aparte del cambio en la manera como las empresas de seguros van a llevar su contabilidad, el nuevo marco contable requiere de un trabajo de implementación significativo en todas sus operaciones. Ello conducirá a la inclusión de nueva tecnología o, a su vez, mejorar la existente, optimizar los métodos y renovar los controles.Para la implementación de este nuevo estándar de calidad en las empresas de seguros, va a ser necesario contar con personal competente interno o contratado externamente no solo para la comprensión del impacto que conlleva la aplicación del nuevo marco contable de las aseguradoras, sino para implementarlo al contexto de los negocios diarios. Las empresas de seguros deberían efectuar proyectos de comunicación con los inversionistas con el motivo de exponer que la implementación de la NIIF 17 acarreará una mayor volatilidad en los resultados financieros, y el capital patrimonial del cual ellos son partícipes, originado por el uso de las tasas de descuento actuales del mercado.
Keywords: INDUSTRIA ASEGURADORA; CONTRATO DE SEGURO Y REASEGURO; NIIF 4; NIIF 17